-8u-6=-6u+6

Simple and best practice solution for -8u-6=-6u+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8u-6=-6u+6 equation:


Simplifying
-8u + -6 = -6u + 6

Reorder the terms:
-6 + -8u = -6u + 6

Reorder the terms:
-6 + -8u = 6 + -6u

Solving
-6 + -8u = 6 + -6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '6u' to each side of the equation.
-6 + -8u + 6u = 6 + -6u + 6u

Combine like terms: -8u + 6u = -2u
-6 + -2u = 6 + -6u + 6u

Combine like terms: -6u + 6u = 0
-6 + -2u = 6 + 0
-6 + -2u = 6

Add '6' to each side of the equation.
-6 + 6 + -2u = 6 + 6

Combine like terms: -6 + 6 = 0
0 + -2u = 6 + 6
-2u = 6 + 6

Combine like terms: 6 + 6 = 12
-2u = 12

Divide each side by '-2'.
u = -6

Simplifying
u = -6

See similar equations:

| 2l+4/3l | | 5+16n=5 | | 2x-6x-3=0 | | 6.2x+1=5.2x | | 2+3*16+1=85 | | 2.5=3.5x | | 64/(15-7)*2-9 | | -4-8(6z+4)=8(4z-7)-1 | | 7r=-1/2 | | f(2+a)=5(2+a)-7 | | h+19/19=2 | | 3=-7 | | 950+700+4x=850+200+9x | | f(4)=5(4)-7 | | +5=1+k | | 11-4x=0.5 | | 19+-5p=-1 | | (3/5)w-(1/7)=(-3/7)w+(3/7) | | 7r=-7 | | 12-(1/26)(2x)=6-(1/26)(x) | | 7x*8k=8x-17k | | 5x+2/7x-6 | | 4y^2-5y^2+7y^2= | | [SQRT(x+3)]=2[SQRT(x)] | | x^3+2x^2-6x=12 | | (5/4)y-(3/8)=(7/2)y+(3/8) | | 0.1=.07+x(0.12) | | 2(x/3-3)=16 | | 3(3n-3)=-54 | | (9x-3)*(-0.7)= | | 6+9z=7 | | -6v+11=-4v+1 |

Equations solver categories